Escola precária: contratos temporários, terceirização na escola pública e as implicações no trabalho das professoras de Educação Física - Lovatto, Guilherme Stürmer (2019)
This work aims to portray the deterioration of labor conditions for physical education teachers in Rio Grande do Sul from the perspective of the precarization of the World of Labor. Using Historical and Dialectical Materialism as a method, we present an outline of the historical development of teachers as a professional category in Brazil – a country of dependent and peripheral capitalism, where precarization is a structural feature of work relations. We point out how temporary employment intensifies the precarization of both teachers’ labor conditions and public schools in the current productivist period in Brazilian education – a period in which structural counter-reforms have been substantially altering the social status of labor and extending the reach of platform capitalism and precarization processes. We analyze how changes in the World of Labor subordinate the specificities of educational labor to the logic of capital accumulation. We also point out how those changes arise from Base Nacional Curricular Comum 1 and competence-based neo-technicist approaches to education, such as the non-place of physical education, forging a new sort of teacher and of pedagogical intellectuality.